Harmonisasi Layanan Digital Dibidang Perpajakan Dalam Meningkatkan Kepatuhan Wajib Pajak - Kurachman, Taufik (Jurnal Pajak dan Bisnis, 2025)
Digital services in taxation are one of the government's efforts to improve efficiency, transparency, and accountability in the taxation system. With the rapid development of digital technology, the government needs to harmonize digital services to anticipate the digital revolution that may affect global taxation dynamics. This study aims to analyze how the harmonization of digital services in taxation can prepare the taxation sector to face the challenges of the digital revolution. The research method used is descriptive qualitative, with a case study approach and in-depth interviews with stakeholders involved in the implementation of digital taxation services. The results show that although the government has developed various digital systems for tax administration, challenges still exist in terms of system integration, infrastructure readiness, and technology adoption by the public. Therefore, digital service harmonization needs to be carried out comprehensively with clear policy support, infrastructure strengthening, and increased digital literacy for the public. This research contributes to understanding the importance of the tax sector's readiness in facing the digital era and the rapidly developing technological revolution